A Review of the Fund's External Communications Strategy. (Policy Papers; Policy Paper ;, 2003)
This paper reviews implementation of the Fund's external communications strategy and suggests issues that the Board may wish to discuss at its third meeting since 1998 on the subject. The strategy has been shaped by the previous Board discussions and more recent decisions and discussions on transparency, conditionality, PRSP/PRGF, the Independent Evaluation Office, and other issues. This paper represents more of a stocktaking than a fundamental reconsideration of the Fund's approach to external communications. It examines the progress made in recent years and steps that might be taken with current resources to increase the effectiveness of the strategy.